The Story of the Hand - Thirkannad, Sunil M.; Patil, Rahul (Indian Journal of Plastic Surgery, 2021)
This review describes the Story of the Human Hand. It traces the functional needs that led to evolution of the human hand as well as its embryological development. The various in utero stages of formation of the human hand are covered along with a description of the various molecular and genetic factors that control this process.
Keywords: embryology; hand; upper extremity; development; limb bud